Reliability analysis of transmission components under elastohydrodynamic lubrication conditions - Dong, Qingbing (2017)
Lubricants are commonly used to improve the tribological performance of mechanical components in power transmission systems. The localized high pressure generated within the lubricants would induce elastic surface deformation and increase the lubricant viscosity. Lubrication with the consideration of these effects is commonly known as elastohydrodynamic lubrication (EHL). In engineering practice, surfaces are always flawed by roughness, which may significantly influence hydrodynamic flows and the entraining action. A complete separation of the contacting interfaces by the lubricating fluid is preferred to enhance the reliabilities and reduce the lifetime cost. However, nowadays technology allows modern machines to operate in more severe conditions, e.g., under heavier loads at higher temperatures or lubricated by lower-viscosity oils, which may result in a thinner lubricant film than the magnitude of the roughness and thus lead to the coexistence of the hydrodynamic lubricant film and asperity contact. Such a lubrication regime is referred to as mixed EHL and has long been recognized. Generally, the materials in contact are assumed to be homogeneous. Many materials, nevertheless, have a heterogeneous structure at a certain level of observation. From an engineering point of view, heterogeneous materials, such as composites, coated materials and other multi-layered materials, are desirable to enhance particular properties of materials. However, the presence of the undesirable defects formed unintentionally during the material manufacturing process, such as inclusions, voids, dislocations and cracks, would result in stress concentrations and consequently lead to fracture and fatigue of materials. Therefore, it is of great significance to take the heterogeneous effects of contact components into consideration for their reliability analysis. In addition, modern machinery is required to operate under severe loading conditions. Such conditions would lead to the plastic evolution of the materials which plays a significant role in their reliability. Analysis of such plastic evolution would thus provide guidance to improve the design of component structures. A semi-analytical solution is first developed for materials with inhomogeneous inclusions subjected to EHL point contact with the consideration of surface roughness. In this solution, the inclusions are homogenized according to Eshelby’s equivalent inclusion method with unknown eigenstrains to be determined. A surface coating layer is also considered and assumed as an inclusion of finite size located on the surface, and thus the same methodology applies. The disturbed surface deformation due to the presence of surface coating and inclusions is iteratively introduced into the lubricant film thickness upon the realization of convergence. The discrete convolution and fast Fourier transform technology is adopted to improve the computational efficiency. Based on this solution, a three-dimensional model of line-contact EHL with inclusions distributed periodically along the contact length direction has been developed upon the implement of an algorithm based on fast Fourier transform technology. Based on the elastic solution of the subsurface stress field, a closed-form solution of plasto-EHL line and point contact for materials with inhomogeneous inclusions is further presented. The plastic strains are iteratively obtained by a procedure involving a plasticity loop and an incremental loading process, and the disturbed deformation caused by the plastic strains along with that caused by the equivalent eigenstrains is introduced to update the lubricant film thickness. The solution takes into account the mutual interactions among inclusions and their surrounding plastic regions, thus leading to an accurate description of the surface pressure distributions, film thickness profiles, plastic zones and subsurface stress field. The solution is then extended to model materials with cracks and inhomogeneous inclusions under plane-strain condition. The crack is modeled by a distribution of edge dislocations with unknown densities according to the distributed dislocation technique. With an assumption that the crack surfaces are not in contact, free surface traction conditions of cracks are employed to formulate the governing equations. Coupled governing equations with unknown equivalent eigenstrains and dislocation densities are established to describe the stress and strain fields beneath the contact surfaces. Stress intensity factors are obtained based on the solution of the dislocation densities. It can be predicted that these solutions have potential applications for the reliability analysis of mechanical components made from composites or with near-surface defects beneath their surfaces, and would provide guidance for minimizing the potential damage of heterogeneous materials induced by embedded inclusions and cracks under lubricated contact.